Dentinoenamel junction: Motif for interfacial mechanics of dissimilar materials - Spencer, P.; Marangos, Orestes; Misra, A. (My University, 2016)
© 2017 Elsevier Ltd. All rights reserved. The dentinoenamel junction provides the connection between material systems of dissimilar compositions and mechanical properties. The characteristics of the region proximal to this junction contributes to the effectiveness of the mechanical performance of this interface. This chapter discusses the current understanding of this junction region with respect to its structure, composition, and mechanical behavior. Some new findings using alternative techniques that permit multiscalar homotopic measurements of composition and mechanical properties are described. Results from preliminary microscale finite element models based on realistic idealizations are then discussed to illustrate the effect of structure and composition on the mechanical behavior. The presented information shows the need for further research from both the characterization and the modeling viewpoints so that the superior properties of this robust junction can be beneficially harnessed.
Keywords: Dentinoenamel junction; Finite element modeling; Homotopic measurements; Micro-Raman spectroscopy; Scanning acoustic microscopy